Live birth after PGD with confirmation by a comprehensive approach (karyomapping) for simultaneous detection of monogenic and chromosomal disorders. - Natesan, SA; Handyside, A; Thornhill, A; Ottolini, C; Sage, K; Summers, M; Konstantinidis, M; Wells, D; Griffin, D (2014)
Preimplantation genetic diagnosis (PGD) for monogenic disorders has the drawback of time and cost associated with tailoring a specific test for each couple, disorder, or both. The inability of any single assay to detect the monogenic disorder in question and simultaneously the chromosomal complement of the embryo also limits its application as separate tests may need to be carried out on the amplified material. The first clinical use of a novel approach ('karyomapping') was designed to circumvent this problem. In this example, karyomapping was used to confirm the results of an existing PGD case detecting both chromosomal abnormalities and a monogenic disorder (Smith-Lemli-Opitz [SLO] syndrome) simultaneously. The family underwent IVF, ICSI and PGD, and both polar body and cleavage stage biopsy were carried out. Following whole genome amplification, array comparative genomic hybridisation of the polar bodies and minisequencing and STR analysis of single blastomeres were used to diagnose maternal aneuploidies and SLO status, respectively. This was confirmed, by karyomapping. Unlike standard PGD, karyomapping required no a-priori test development. A singleton pregnancy and live birth, unaffected with SLO syndrome and with no chromosome abnormality, ensued. Karyomapping is potentially capable of detecting a wide spectrum of monogenic and chromosome disorders and, in this context, can be considered a comprehensive approach to PGD.